2019
DOI: 10.1111/1742-6723.13356
|View full text |Cite
|
Sign up to set email alerts
|

Impact of electric scooters to a tertiary emergency department: 8‐week review after implementation of a scooter share scheme

Abstract: Objective: A retrospective audit of presentations to a tertiary trauma centre reviewing the demographics of electric scooter injuries in the first 2 months of the scooter-share scheme, which was commenced in Brisbane in November 2018. Methods: Electric scooter-associated presentations to the Royal Brisbane and Women's Hospital Emergency and Trauma Centre from November 2018 to January 2019 were identified. Data collected included patient demographics, type and location of injuries, helmet use, alcohol consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
99
5
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(131 citation statements)
references
References 2 publications
18
99
5
9
Order By: Relevance
“…Mitchell et al . performed a retrospective audit of e‐scooter related encounters at a single ED in Brisbane, Australia, which showed contusions/abrasions and fractures/dislocations were the most common injuries . In the present study of e‐scooter related presentations, 78% of patients required X‐rays, and 24% required CT scans.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Mitchell et al . performed a retrospective audit of e‐scooter related encounters at a single ED in Brisbane, Australia, which showed contusions/abrasions and fractures/dislocations were the most common injuries . In the present study of e‐scooter related presentations, 78% of patients required X‐rays, and 24% required CT scans.…”
Section: Introductionmentioning
confidence: 63%
“…The recent work by Mitchell et al . also reported on 54 e‐scooter injuries in their study in the first 2 months following the introduction of an e‐scooter sharing service to Brisbane.…”
Section: Discussionmentioning
confidence: 82%
“…Various factors contribute to the prevalence of e-scooter injuries: Incompatible infrastructure (e.g., lack of bike lanes), lack of directional tools on e-scooters (e.g., turn signals, headlights), rider inexperience and noncompliance with age restrictions, failure of users to obey traffic rules, alcohol use, and reluctance to wear helmets [5,7,24,28,33]. Recent studies have found helmet use among injured e-scooter riders to be extremely low, ranging from 0% and 8% in most studies [5,6,23,24,28,34,35,39]. Additionally, despite regulations prohibiting them from doing so, e-scooter users commonly ride and park on sidewalks, which can lead to injuries to users as well as to pedestrians [40,41].…”
Section: Injuriesmentioning
confidence: 99%
“…A primary public health concern, and the focus of the vast majority of academic research on e-scooters to date, is e-scooter-related injuries [10]. Several studies in the United States and elsewhere have found a high incidence of injuries related to scooter usage, particularly head and limb trauma, after the introduction of e-scooter share programs [5,12,24,28,[33][34][35]. There is even some evidence that the injury rate for e-scooters may be higher than that of motorcycles and personal vehicles [27,36].…”
Section: Injuriesmentioning
confidence: 99%
“…This issue of the journal we publish a report analysing electric scooter injuries in Brisbane; another paper on injuries in Dunedin is in the production pipeline and will be published soon. Emergency physicians know better than most, that life carries risk.…”
Section: Competing Interestsmentioning
confidence: 99%